2′, 4-Dihydroxy-3′, 4′, 6′-trimethoxychalcone from Chromolaena odorata possesses anti-inflammatory effects via inhibition of NF-κB and p38 MAPK in lipopolysaccharide-activated RAW 264.7 macrophages. (2nd January 2018) - Dhar, Rana; Kimseng, Rungruedee; Chokchaisiri, Ratchanaporn; Hiransai, Poonsit; Utaipan, Tanyarath; Suksamrarn, Apichart; Chunglok, Warangkana
Abstract: Context: Immune dysregulation has been implicated in the pathogenesis of many diseases. Macrophages play a crucial role contributing to the onset, progression, and resolution of inflammation. Macrophage inflammatory mediators are of considerable interest as potential targets to treat inflammatory diseases. Objective: The present study was conducted to elucidate the anti-inflammatory mechanism of 2′, 4-dihydroxy-3′, 4′, 6′-trimethoxychalcone (1 ), the major chalcone isolated from Chromolaena odorata (L.) R.M.King & H.Rob, against lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 macrophages. Materials and methods: Cell viability, nitric oxide (NO), and proinflammatory cytokines of LPS-activated RAW 264.7 cells were measured by MTT, Griess, and ELISA assays, respectively. Cell lysates were subjected to Western blotting for investigation of protein expression. Results and discussion: Treatment with the major chalcone1 significantly attenuated the production of NO and proinflammatory cytokines, tumor necrosis factor-α, interleukin-1β, and interleukin-6 in a dose-dependent manner. The chalcone suppressed nuclear factor-κB (NF-κB) stimulation by preventing activation of inhibitor κB kinase (IKK) α / β, degradation of inhibitor κB (IκB) α, and translocation of p65 NF-κB into the nucleus. Additionally, the chalcone markedly repressed the phosphorylation of p38 mitogen-activated protein kinase (MAPK), but no further inhibition was detected for c-Jun N-terminal activated kinases or extracellular regulated kinases. Thus, suppression of NF-κB and p38 MAPK activation may be the core mechanism underlying the anti-inflammatory activity of 2′, 4-dihydroxy-3′, 4′, 6′-trimethoxychalcone (1 ). Conclusion: These findings provide evidence that 2′, 4-dihydroxy-3′, 4′, 6′-trimethoxychalcone (1 ) possesses anti-inflammatory activity via targeting proinflammatory macrophages. This anti-inflammatory chalcone is a promising compound for reducing inflammation.